2022
DOI: 10.1111/aos.15156
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of neuroretinal integrity in optical coherence tomography‐graded eyes with partial‐thickness macular holes

Abstract: Purpose: To evaluate neuroretinal integrity in different subtypes of optical coherence tomography (OCT)-graded partial-thickness macular holes. Methods: Fovea-centred SD-OCT images (Cirrus, Carl Zeiss Meditec AG; Spectralis, Heidelberg Engineering GmbH) and visual acuity (VA) acquired at every visit were analysed by two retina specialists retrospectively in 71 eyes of 65 patients. Partial-thickness macular holes were classified as lamellar macular hole (LMH), epiretinal membrane foveoschisis (ERMF) or macular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Thus, a complete anatomical and visual regression was never reported at 1 year following non-surgical, non-invasive treatment. Stino et al (2022) recently described the time-course following partial thickness macular holes. In this study epi-retinal proliferation was associated with worsening of visual acuity, which was accompanied by neuro-retinal tissue loss with wider foveal cavities and thinner foveal floors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a complete anatomical and visual regression was never reported at 1 year following non-surgical, non-invasive treatment. Stino et al (2022) recently described the time-course following partial thickness macular holes. In this study epi-retinal proliferation was associated with worsening of visual acuity, which was accompanied by neuro-retinal tissue loss with wider foveal cavities and thinner foveal floors.…”
Section: Discussionmentioning
confidence: 99%
“…Some observational case series suggest that LMH are relatively stable conditions [ 47 , 93 , 108 , 109 , 110 ]. Forty one eyes were followed for an average of 37 months with time domain OCT. LMH were diagnosed according to the following four criteria: irregular central foveal thinning, opening of the inner foveal layers, intraretinal splitting and intact foveal photoreceptors [ 8 , 25 , 108 ].…”
Section: Natural Historymentioning
confidence: 99%
“…A recent retrospective longitudinal case series, which used the recent classification proposed by Hubschman et al [ 17 ], reported that visual acuity remained stable in eyes with ERM foveoschisis, LMH and MPH. These eyes had a mean follow up of 10, 11 and 19 months, respectively [ 109 ].…”
Section: Natural Historymentioning
confidence: 99%